(untitled) (Discourse of Law and Administration, 2021)
HM Land Registry introduces the ground-breaking Digital Street Project. The project was announced in HM Land Registry Business Strategy 2017-2022. HM Land Registry aims to introduce digital technology to make purchase and sale of property simpler and easier as well as providing an absolute guarantee of ownership. It is planned to use Artificial Intelligence in conveyancing and registration. Blockchain is planned to enable the register to be distributed among trusted parties such as lenders and conveyancers, giving them the ability to operate and update in a secure and tamper-proof manner. There are first results of this project. First digital mortgage was signed and registered in April 2018. More than 10 000 digital mortgages have already been registered. First conveyancing deed was signed and registered in July 2020.